Penerapan Konsep Green Hotel di Nusa Lembongan Bali - Putu Gede Eka Darmaputra; Dewa Ayu Lily Dianasari; Ida Ayu Kalpikawati (JURNAL BISNIS HOSPITALITI, 2020)
Nusa Lembongan is currently one of the favorite tourist attractions among foreign and domestic tourists because of its pristine natural beauty. As one of the areas in Klungkung Regency, Bali Nusa Penida also provides accommodation in both star and non-star hotels, villas, bungalows, and homestays. This study aims to determine the implementation of the green hotel concept in Nusa Lembongan Bali. Data was collected by distributing questionnaires to 47 accommodations in Nusa Lembongan by means of purposive sampling. The results of the study show the following: hotel perceptions and assessments of environmental policies and actions (4.23), use of environmentally friendly products (4.39), collaboration with local communities and organizations (4.27), resource development (3.91) , solid waste treatment system (3.99), energy efficiency (3.96), efficiency and water quality (3.97).